2011
DOI: 10.1007/s12012-011-9136-9
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H:Quinone Oxidoreductase 1 and its Potential Protective Role in Cardiovascular Diseases and Related Conditions

Abstract: NAD(P)H: quinone oxidoreductase (NQO) represents a family of flavoproteins that catalyze the two-electron reduction of quinones and their derivatives. In mammalian systems, there are two members of NQO, namely, NQO1 and NQO2. NQO1 utilizes NAD(P)H, whereas NQO2 employs dihydronicotinamide riboside (NRH) as the electron donors. In addition to the well-documented action in reducing quinone compounds and preventing the formation of reactive oxygen species, NQO enzymes, especially NQO1 also possess other important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…In addition, NQO1 possesses many other biological activities, such as scavenging of superoxide anion radicals and stabilization of the tumor-suppressor p53, which may serve as the basis for its potential involvement in protecting against disease processes. 64 However, despite these various roles of NQO1, mice lacking NQO1 gene expression showed no detectable phenotype and were indistinguishable from WT mice, although NQO1 null mice exhibited increased toxicity when administered menadione compared with WT mice. 65 It is plausible that in NQO1 null mice NQO2 may compensate for the loss of NQO1 65 and thus may not worsen renal dysfunction compared with WT even in cisplatin-induced acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NQO1 possesses many other biological activities, such as scavenging of superoxide anion radicals and stabilization of the tumor-suppressor p53, which may serve as the basis for its potential involvement in protecting against disease processes. 64 However, despite these various roles of NQO1, mice lacking NQO1 gene expression showed no detectable phenotype and were indistinguishable from WT mice, although NQO1 null mice exhibited increased toxicity when administered menadione compared with WT mice. 65 It is plausible that in NQO1 null mice NQO2 may compensate for the loss of NQO1 65 and thus may not worsen renal dysfunction compared with WT even in cisplatin-induced acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression data showed that DDT increased hepatic NQO1 expression compared to the control group. NQO1 is a gene induced by a wide variety of chemicals, including oxidants, xenobiotics, electrophiles, and phenolic compounds (Zhu, Li, 2012). This gene is involved in the body's defense system against oxidative stress (Gaikwad et al, 2001) and its up-regulation may be an adaptive mechanism to protect against oxidative and inflammatory stress.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is involved in the body's defense system against oxidative stress (Gaikwad et al, 2001) and its up-regulation may be an adaptive mechanism to protect against oxidative and inflammatory stress. NQO1 may also play a role in lipid metabolism and insulin resistance (Zhu, Li, 2012), since its expression levels have been positively correlated with adiposity, glucose tolerance, and markers of liver dysfunction, suggesting a possible involvement of NQO1 in the metabolic complications of human obesity (Palming et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…NQO1 has also been implicated in the formation of semiquinone radicals of anthracyclines in an aerobic environment [27,94], noting, however, that the deoxyaglycone metabolite is the predominant metabolite under anaerobic conditions [99]. Interestingly, NQO1 is predominantly found in the cytosol of cells [99], with the highest levels of the enzyme found in cardiovascular tissues and the liver [119].…”
Section: A) Nqo1mentioning
confidence: 99%
“…While Nrf2 is a critical transcription factor involved in cellular protection from toxic xenobiotics, it is kept at low levels under unstressed conditions by Keap1 [121]. The promoter region of the NQO1 gene contains multiple antioxidant response elements (AREs) and a xenobiotic response element (XRE) [119,120] that bind Nrf2 and regulate NQO1 expression. Nrf2 has been implicated in chemotherapy drug resistance in vitro.…”
Section: A) Nqo1mentioning
confidence: 99%